Q’inqu: Inclusive Board Game for the Integration of People with Disabilities - Jadán-Guerrero, Janio (2020)
The educational inclusion of people with disabilities continues to be a great challenge for society. Due to the field’s diversity and complexity, people with disabilities have few opportunities to be integrated into educational activities or even entertainment. This article describes a novel educational resource developed within the field of applied technologies. Q’inqu is an inclusive board game that encourages the family and educational inclusion of people with disabilities. Q’inqu is a Quechua word meaning “Labyrinth”. This is a metaphor for the challenges faced by families living with a person with disabilities, and it also reflects its narrative structure based on the “Legend of the Incas’ treasure”. Q’inqu has the general theme of a traditional board game where turns are taken until the treasure is found. What makes it different is the integration of inclusive elements through the use of technology. There are cards with a braille code, a rectangular board with high relief, and a circular board with textures. An App reads QR codes and also patterns, which present additional information based on augmented reality. These features provide support to blind players and to those who are unable to read, making the game both entertaining and educational. Q’inqu was developed and tested by a multidisciplinary team of 80 people, which included students and professionals from design, education and pedagogy. The most relevant result was that out of 367 ideas that were presented, it was awarded first prize in the category Toys for children with disabilities in the CMA contest held in Ecuador. © 2020, Springer Nature Switzerland AG.